Faktor-Faktor Dominan Yang Mempengaruhi Jemaat Tidak Mendengarkan Khotbah di GKPI Jemaat Khusus Maranatha Tambunan - Louis M. Tambunan; Ibelala Gea; Nurelni Limbong; Bernhardt Siburian; Megawati Manullang (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
The purpose of this study was to determine the dominant factors that influence the congregation not listening to the sermon. Sermons are central to worship, because the purpose of sermons is to preach the word of God to the congregations and to answer the problems faced by the congregations. The method used in this study is a qualitative research method. With the existence of research methods, it can make it easier for researchers to find problems and solve the problems being studied. Naturally, research methods are interpreted to obtain data that have certain purposes and uses. The results of this study indicate that Worship is a command from God that must be carried out by everyone who has been redeemed and saved by the Lord Jesus Christ. The worship that is carried out is a sign of respect that is carried out in the form of going to church, praying, reading and listening to the word of God, praising God and giving offerings to God. The benefits of attending Sunday worship are that serious worship is not only about doing spiritual things mechanically, but also about understanding and experiencing the spiritual values ​​contained in the worship. And the dominant factor that occurs in these congregations is that they often feel bored quickly so they prefer to play on their cellphones, fall asleep, and leave worship to relieve boredom. Sincerity in participating in worship must be accompanied by sincere intentions and sincerity of heart so that the meaning and benefits can be fully felt.